The Aşik-Zakir Relations in the Alevi-Bektashi Tradition: The Example Of Asik Ummanî of Sivas (Journal of Alevism-Bektashism Studies, 2017)
In the Alevi-Bektashi tradition, the service of “zakir”, one of the twelve services, is one of the key elements of “cem”s. During a “cem”, “zakir” stands right beside “dede” and takes an effective part in the “cem” saying hymns (“nefes”) accompanied by “saz”. Within tradition, “zakirs” are separated into two groups: “zakir”s who just say hymns that belong to folk poets as Shah Hatayi, Pir Sultan Abdal, Kul Himmet, and “zakirs” who both say hymns and are poets (“asik”). Especially those from the second group who are led by a sacred dream to become an “asik”, in other words, whose source of inspiration is sacred and who will become “zakir”in due course, are very respected within community. Asik Ummani, who is the subject of this paper, is an Alevi-Bektashi folk poet born and raised in Sivas region, and he was led by a sacred dream to become an “asik”. Connected to Aguicen “ocak” (one of the Alevi “ocak”s), AsıkUmmani served as “zakir” at “cem”s. Since 1992, he has been serving as “zakir” of Haci Bektash Veli “ocak” at “cem”s In this paper, we begin with an analysis of Asik Ummani’s life, his “asik” and literary identity and his poetry, and then, we focus on his service as “zakir” at “cem”s. Information about his life and poems was gathered from the interview with him. His poems were analyzed in terms of their form, language, style and content. While dealing with the subjects concerning social life in his poems, Ummani focuses usually on the subjects such as belief structure, doctrines, customs, and worldview of the Alevi-Bektashi tradition. In the course of our analysis, the focus was on the place of these poems in Alevi-Bektashi literature and their effect on the socio-cultural life. Also, some points are made about the period in which “asik”sof the Alevi-Bektashi tradition are becoming “zakir”s.